Association of possible osteopetrosis with acute myeloid leukaemia in a child. (6th August 2013) - Prasad, Rajniti; Jaiswal, B P; Mishra, O P; Singh, Utpal Kant
Abstract : Osteopetrosis is a rare disease characterised by an increase in bone mass, skeletal malformations and bone marrow failure due to defective bone resorption. We report a 3-month-old male child presented with chest infections, failure to thrive and hepatosplenomegaly and diagnosed with osteopetrosis associated with acute myeloid leukaemia M3 type (AML-M3 ). The patient died on day 7 of admission due to respiratory failure. To our knowledge, this is the first case where both osteopetrosis and AML is diagnosed in a patient.